ЎРТА АСРЛАРДА ХОРАЗМ ВОҲАСИДАГИ ТАЪЛИМ ВА МАЪРИФАТПАРВАРЛИК - Турганов, Б.К.; Мадреймов, Ф.М. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of education of highly-developed generation on the territory of Great Turan, that are considered to be an important means of the development of the society.